Claudin expression in the bone-lining cells of female rats exposed to long-standing acidemia - Kannikar Wongdee (2018)
Besides enhancing osteoclast-mediated bone resorption, chronic metabolic acidosis (CMA) induces mineral efflux across the epithelial-like bone membrane formed by bone-lining cells (inactive osteoblasts), possibly via the paracellular pathway. However, there was a compensatory mechanism that restricted bone loss in the late phase of CMA, and changes in the expression of claudins, which are tight junction proteins known to regulate epithelial barrier function, were therefore anticipated in bone-lining cells. Herein, primary rat osteoblasts were found to express several transcripts of claudins, i.e., claudin-5, -11, -14, -15 and -16. Their protein expressions in bone-lining cells were demonstrated by immunohistochemistry in decalcified tibial sections. After exposure to CMA induced by oral administration of 1.5% NH4Cl for 21 days, expression of claudin-14, which normally seals the paracellular space and restricts ion movement, was increased, whereas that of claudin-15 and -16 which form pores for ion transport were decreased. Expressions of claudin-5 and -11 were not changed by CMA. In conclusion, the bone-lining cells of rats exposed to CMA for 21 days upregulated an ion-restrictive claudin (i.e., claudin-14), while downregulating ion-permeable claudins (i.e., claudin-15 and -16). These cellular responses might be parts of a compensatory mechanism accounting for deceleration of bone loss in late CMA. © 2009 Elsevier Inc.